Diplomasi Olahraga PSSI Sebagai Organisasi Nonpemerintah Dalam Penyelenggaraan Piala Dunia U-17 FIFA 2023 - Musyaffa, Hanif; Yulianti, Dina; Pratisti, Siti Aliyuna; Mubarok, Kiagus Zaenal (Universitas Komputer Indonesia, 2024)
This article discusses the sports diplomacy carried out by the Indonesian Football Association (PSSI) as a Non-Governmental Organization (NGO) in organizing the 2023 FIFA U-17 World Cup. Utilizing research by Ari et al. (2018), which identifies five tools in sports diplomacy—international sports organizations, national brand, media and technology, sports ambassadors, and lobbying activities—the researcher employed a qualitative methodology using data from literature sources such as research articles, mass media news, and relevant documents. The research findings indicate that PSSI effectively utilized these tools, leading to the conclusion that sports diplomacy was successfully conducted during the implementation of the FIFA U-17 World Cup 2023.